Analisis Penggelolaan Persediaan Untuk Peningkatan Efisiensi Biaya Produksi Air Mineral (Studi Kasus PT. Pintar Sumber Mineral) - Mitan, Virjinia Martha; Herdi, Henrikus; Jaeng, Wihelmina M. Yulia (Universitas Nusa Nipa Maumere, 2026)
This study aimed to analyse the mineral water inventory management practices and improve production cost efficiency at PT. Pintar Sumber Mineral. The research utilized a quantitative descriptive method, with data collected through interviews, documentation reviews, and literature studies. The findings demonstrated that the company had successfully and effectively implemented the Economic Order Quantity (EOQ) model. This effective implementation was evidenced by: The increase in the EOQ value corresponding with the growth in annual demand. The implementation of specific inventory management strategies that supported cost efficiency. While significant demand growth led to an increase in ordering and holding costs, the strategy of adjusting the EOQ model was able to optimally mitigate the impact of these rising costs. This study concluded that the application of the EOQ model had made a positive contribution to the company's operational efficiency.